Komposisi jenis kelamin anak, program Keluarga Berencana dan fertilitas - Mugia Bayu Raharja; Robani Catursaptani; Rahmadewi Rahmadewi (Jurnal Kependudukan Indonesia, 2021)
The number and sex composition of children are important for some married couples in Indonesia. Having sons in the family is considered as a must since they are argued to be the successor of the family lineage. The presence of daughters is expected to help with household chores and care for their elderly parents. The sex preference for children by the married couples can affect their number of children. This study aims to assess the relationship between the number and sex composition of children, contraceptive use, and the desire to have more children among women in Indonesia. The study employed the data from the 2017 Indonesian Demography and Health Survey (IDHS), with the unit of analysis of currently married women aged 15-49 who have at least one living children. The results show that women with two or more children of the same sex had a higher tendency to have additional children and no use of contraceptives. The Family Planning program's campaign of similar values shared between son and daughter is still hardly accepted, hence, sex preference still exists. It is necessary to reformulate an effective concept for proper socialization of these values as an effort to control the fertility rate in Indonesia.